2021
DOI: 10.3390/healthcare9111429
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Rehabilitation’s Impact on Negative Symptoms and Psychosocial Rehabilitation in Schizophrenia Spectrum Disorder: A Systematic Review

Abstract: Background: Schizophrenia is a chronic psychiatric disorder with symptoms that can severely affect patients’ quality of life. While drug administration inhibits most of the positive symptoms, it fails to effectively treat the negative symptoms and in turn relies on rehabilitation therapies. With technological progress, virtual reality (VR) has been the target of recent studies in terms of mental health rehabilitation and has been shown to be a tool with ecological validity in order to introduce the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…People diagnosed with schizophrenia may experience significant difficulties in social cognitive functioning, including problems with understanding actions, emotions, social perception, and/or empathy [ 113 ]. Some of the psychotic symptoms, i.e., hallucinations and delusions, are partially alleviated by antipsychotic drugs, but social impairments are a significant problem, complicating the path to health stability/recovery [ 114 ]. In general, the use of antipsychotic drugs has reduced effectiveness on the negative symptoms of schizophrenia.…”
Section: Virtual Reality (Vr) Therapy For Patients With Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…People diagnosed with schizophrenia may experience significant difficulties in social cognitive functioning, including problems with understanding actions, emotions, social perception, and/or empathy [ 113 ]. Some of the psychotic symptoms, i.e., hallucinations and delusions, are partially alleviated by antipsychotic drugs, but social impairments are a significant problem, complicating the path to health stability/recovery [ 114 ]. In general, the use of antipsychotic drugs has reduced effectiveness on the negative symptoms of schizophrenia.…”
Section: Virtual Reality (Vr) Therapy For Patients With Schizophreniamentioning
confidence: 99%
“…These symptoms are associated with negative effects on the patient’s functional status and quality of life. The clinical expression of negative symptoms is less pronounced compared to positive symptoms, as they may be masked by positive symptoms and may coexist with or be confused with affective symptoms or cognitive disorders [ 114 , 115 ]. The above dysfunctions affect patients’ daily functioning.…”
Section: Virtual Reality (Vr) Therapy For Patients With Schizophreniamentioning
confidence: 99%
“… 53 In treatment, transcranial stimulation of the cerebellum may be in the pipeline. 54 Moreover, using virtual reality to simulate real-world goal-directed behaviors, 55 or smartphone-based ecological momentary interventions designed to increase reward sensitivity and motivation could potentially augment treatment effects. 56 It is imperative that future clinical and research efforts target apathy and its detrimental consequences.…”
Section: Future Directionsmentioning
confidence: 99%
“…Serious games are considered appropriate interventions in mental health care, including for the general population and patients with or without psychiatric concerns [41][42][43]. Studies have reported that serious games influence depression [44,45]; however, a systematic review and meta-analysis focusing on the effect size of a serious game on depression in older adults is rare.…”
Section: Various Interventions Of Serious Games Have Been Conductedmentioning
confidence: 99%